Regulation of Signal Transduction and Role of Platelets in Liver Regeneration. (3rd July 2012) - Nowatari, Takeshi; Fukunaga, Kiyoshi; Ohkohchi, Nobuhiro
Abstract : Among all organs, the liver has a unique regeneration capability after sustaining injury or the loss of tissue that occurs mainly due to mitosis in the hepatocytes that are quiescent under normal conditions. Liver regeneration is induced through a cascade of various cytokines and growth factors, such as, tumor necrosis factor alpha, interleukin-6, hepatocyte growth factor, and insulin-like growth factor, which activate nuclear factor κ B, signal transducer and activator of transcription 3, and phosphatidyl inositol 3-kinase signaling pathways. We previously reported that platelets can play important roles in liver regeneration through a direct effect on hepatocytes and collaborative effects with the nonparenchymal cells of the liver, including Kupffer cells and liver sinusoidal endothelial cells, which participate in liver regeneration through the production of various growth factors and cytokines. In this paper, the roles of platelets and nonparenchymal cells in liver regeneration, including the associated cytokines, growth factors, and signaling pathways, are described.